The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1007/s00381-015-2779-2
|View full text |Cite
|
Sign up to set email alerts
|

Excellent functional outcome following selective dorsal rhizotomy in a child with spasticity secondary to transverse myelitis

Abstract: This report raises the possibility that the use of SDR could be expanded to include other pathologies. We discuss the case and the relevant literature. Our spasticity service at NUH has to date inserted 300 baclofen pumps and performed 60 SDRs mainly in children with cerebral palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
(16 reference statements)
0
2
0
Order By: Relevance
“… 7 Although CP diagnosis was one of the inclusion criteria of this review, SDR can also be indicated for patients with spasticity resulting from other diagnoses such as multiple sclerosis, Leigh syndrome, 25 stroke, 26 spinal cord injury 24 , and transverse myelitis. 27 …”
Section: Data Synthesismentioning
confidence: 99%
“… 7 Although CP diagnosis was one of the inclusion criteria of this review, SDR can also be indicated for patients with spasticity resulting from other diagnoses such as multiple sclerosis, Leigh syndrome, 25 stroke, 26 spinal cord injury 24 , and transverse myelitis. 27 …”
Section: Data Synthesismentioning
confidence: 99%
“…This treatment reduces the sensory input into spinal-motorneuron pools, reducing their excitability. 18 , 19 Orthopedic surgery (tendon lengthening, soft tissue release, and osteotomies) may be considered in patients with upper and lower limb spasticity after stroke, particularly for equinovarus foot deformity, improving kinetic and kinematic gait parameters. 20 However, further validation of surgical correction of spastic foot following stroke is desirable with higher level of study designs and validated assessment tools.…”
Section: Management Of Poststroke Spasticitymentioning
confidence: 99%